2018
DOI: 10.3168/jds.2017-13565
|View full text |Cite
|
Sign up to set email alerts
|

High-grain diets supplemented with phytogenic compounds or autolyzed yeast modulate ruminal bacterial community and fermentation in dry cows

Abstract: The feeding of concentrate-rich diets may lead to microbial imbalances and dysfermentation in the rumen. The main objective of this study was to determine the effects of supplementing phytogenic compounds (PHY) or autolyzed yeast (AY) on rumen fermentation and microbial abundance in cows intermittently fed concentrate-rich diets. The experiment was carried out as an incomplete 3 × 4 Latin square design, with 8 nonlactating rumen-fistulated Holstein-Friesian cows. The cows were randomly assigned to a concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
48
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(60 citation statements)
references
References 45 publications
(80 reference statements)
10
48
1
Order By: Relevance
“…Recent research of our team has shown that intermittent SARA affects pH and causes important bacterial shifts in the rumen. These effects were stronger during the first versus the second SARA bout, despite feeding the same diet (Neubauer et al, 2018). Most interestingly, this research showed that supplementation of phytogenic compounds (PHY) or autolyzed yeast (AY) alleviated the dysbiosis mainly by reducing the drop of ruminal pH, promoting chewing activity, and beneficially affecting microbial community structure.…”
Section: Introductionmentioning
confidence: 75%
See 4 more Smart Citations
“…Recent research of our team has shown that intermittent SARA affects pH and causes important bacterial shifts in the rumen. These effects were stronger during the first versus the second SARA bout, despite feeding the same diet (Neubauer et al, 2018). Most interestingly, this research showed that supplementation of phytogenic compounds (PHY) or autolyzed yeast (AY) alleviated the dysbiosis mainly by reducing the drop of ruminal pH, promoting chewing activity, and beneficially affecting microbial community structure.…”
Section: Introductionmentioning
confidence: 75%
“…Moreover, a decrease in plasma lysoPC has been previously reported in cows receiving LPS from E. coli (O26:B6) intramammarily or experiencing diseases (Hailemariam et al, 2014b;. However, as PC are generally associated with cholesterol to surround triacylglycerols (Gruffat et al, 1996), their decrease might be a common observation in cows receiving high-concentrate diets, as feeding high levels of fermentable carbohydrates is generally associated with a decreased production of acetate (Neubauer et al, 2018), the main precursor of cholesterol synthesis in ruminants (Liepa et al, 1978). Moreover, SM are part of bovine phospholipids of very low-density lipoproteins (Nilsson and Duan, 2006).…”
Section: Effect Of Intermittent Sara Challengementioning
confidence: 99%
See 3 more Smart Citations